2019
DOI: 10.1136/bcr-2019-229718
|View full text |Cite
|
Sign up to set email alerts
|

Disappearing nodules: spontaneously regressing pulmonary amyloidosis

Abstract: A case report of spontaneous regression of pulmonary amyloidosis, diffuse interstitial pattern, in an elderly patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The favourable clinical and radiological evolution with the disappearance of all symptoms, including dyspnoea and cough, was atypical. Although reports have shown that secondary amyloidosis can completely resolve with treatment, few cases of pulmonary amyloidosis have spontaneously resolved [14,15] . To our knowledge, our case of pulmonary cystic amyloidosis is unique [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The favourable clinical and radiological evolution with the disappearance of all symptoms, including dyspnoea and cough, was atypical. Although reports have shown that secondary amyloidosis can completely resolve with treatment, few cases of pulmonary amyloidosis have spontaneously resolved [14,15] . To our knowledge, our case of pulmonary cystic amyloidosis is unique [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Although reports have shown that secondary amyloidosis can completely resolve with treatment, few cases of pulmonary amyloidosis have spontaneously resolved [14,15] . To our knowledge, our case of pulmonary cystic amyloidosis is unique [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%